Utilizing Various Online Dictionaries to Improve the English Diphthong Pronunciation Ability of the PGRI Payangan Vocational Students - Puspani, Ida Ayu Made; Indrawati, Ni Luh Ketut Mas; Sukarini, Ni Wayan; Mulyana, Novita (Lingual Journal of Language and Culture; Vol 14 No 2 (2022): Lingual: Journal of Language and Culture, 2022)
The difference in the pronunciation system between English and Balinese, which is the mother tongue of the Balinese people, is often a problem. One of the most common types of pronunciation difficulties is thepronunciation of diphthongs in English. Pronunciation errors will certainly have an impact on misunderstandings during English communication.Based on this phenomenon, this study is aimed at providing a solution to improve the ability to pronounce diphthongs in English, which is by utilizing various online dictionaries that are equipped with audio features. This solution is one of the options that can be done considering that currently, Balinese people are very close to technology, but some still are not able to fully utilize the dictionary in the network. The target of this study was the students of SMK PGRI Payangan Gianyar. Keywords: diphthong, online dictionary, community service